A novel hybrid approach for “Scarless” (at the neck) lateral neck dissection for papillary thyroid carcinoma: A case series and literature review - Chen, Zhen-Xin; Chen, Jing-Bao; Pang, Feng-Shun; Lin, Zhan-Hong; Zhang, Xiao-Bo; Cai, Bei-Yuan; Zheng, Wei-Wu; Cao, Ying; Qin, You (Frontiers in Oncology, 2022)
Lateral neck dissection (LND) is a necessary treatment for thyroid cancer with lateral lymph node metastasis. However, the defect created during open surgery leaves a visible scar on the neck. With advancements in surgical technology, many robotic and endoscopic surgical techniques have been reported as alternatives to open surgery. In this study, we present a case series demonstrating the successful application of a novel hybrid approach for endoscopic LND and a review of different surgical approaches for “scarless” (at the neck) LND. We performed endoscopic LND via a combined chest and transoral approach in 24 patients between January 2021 and March 2022. The surgery was completed successfully in all patients with an average operation time of 298.1±72.9 min. The numbers of positive/retrieved lymph nodes at levels II, III-IV, and VI were 0.7±0.9/8.4±4.1, 3.6±2.7/19.5±6.8, and 4.9±3.9/10.3±4.5, respectively. Complications included transient hypoparathyroidism in 10 patients, transient recurrent laryngeal nerve injury in 1 patient, internal jugular vein (IJN) injury in 1 patient, IJN sacrifice due to cancer invasion in 1 patient, and chyle leak in 1 patient, and no cases of tumor recurrence were observed during follow-up. The present case series indicates that the combined chest and transoral approach is feasible and effective for performing LND. Our review of different approaches for “scarless” (at the neck) LND identified advantages and disadvantages for all techniques. Our novel approach has unique advantages, and thus, it can provide an ideal surgical procedure for specific papillary thyroid carcinoma patients.